1997
DOI: 10.1111/j.1524-4725.1997.tb00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Suspension-assisted Q-switched Nd:YAG Laser Hair Removal

Abstract: Topical suspension-assisted Q-switched Nd:YAG laser therapy reduces hair density after a single treatment. Advantages include its speed, technical ease, and minimal adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 9 publications
0
83
0
2
Order By: Relevance
“…5). The experiment at the study center was identical to the shaving experiment noted above except that five treatments at 4-week intervals were done with the Q-switched Nd:YAG laser (SoftLight, ThermoLase Corporation, San Diego, CA) in conjunction with a topical carbon suspension as previously described [15,16]. Twelve subjects with two test sites each were involved.…”
Section: Methodsmentioning
confidence: 99%
“…5). The experiment at the study center was identical to the shaving experiment noted above except that five treatments at 4-week intervals were done with the Q-switched Nd:YAG laser (SoftLight, ThermoLase Corporation, San Diego, CA) in conjunction with a topical carbon suspension as previously described [15,16]. Twelve subjects with two test sites each were involved.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment was done with a Q-switched Nd:YAG laser (SoftLight, ThermoLase Corporation, San Diego, CA) in conjunction with a topical carbon suspension as previously described [4,[6][7][8]. Briefly, a topical carbon-based suspension was applied to the skin surface and allowed to absorb for several minutes; the excess was removed.…”
Section: Materials and Methods Q-switched Nd:yag Laser Studymentioning
confidence: 99%
“…Electrolysis is a laborious procedure, and incomplete follicular destruction has resulted in keratin granulomas and pseudofolliculitis barbae. Selective follicular damage or destruction has been demonstrated with a variety of laser systems, including ruby lasers, 9,10 diode lasers, 11 alexandrite lasers, 12 Nd:YAG lasers, 13,14 and a pulsed noncoherent light source. 15 Although all of these systems have been shown to be effective in delaying hair regrowth, recent studies have demonstrated that some pulsed laser and light-source hair-removal systems are capable of producing a permanent reduction in hair density in the treated areas.…”
Section: Discussionmentioning
confidence: 99%